¿Compañeras o acompañantes?: mujeres Menonitas misioneras en Argentina = Companions or companions? : missionary Mennonite women in Argentina - Altman, Agustina (Ciencias sociales y religión, 2015)
The aim of this paper is to explore the role of mennonite missionary women in Argentina since their arrival to the country in 1917 until the 1960s. Mennonites are part of the Anabaptist Christians emerged in the sixteenth century, under the radical reform movements. Due to persecutions they migrated to Easter Europe and the United States. From the latter and within the context of a renewal process of the Mennonite Church (MC), it gave rise to the Argentinean mission. Using different sources: diaries, letters, publications, administrative reports, we seek to reconstruct the role, often made invisible, of women in the missionary enterprise. In this way, not only we seek to contribute to a better understanding of the missionalization process but also, to the debate about the ideas and practices of gender in the context of Christianity in the first half of the twentieth century.